2017
DOI: 10.1590/1980-5918.030.001.ao05
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective parameters in paediatric respiratory conditions: cultural adaptation to Portuguese population

Abstract: Introduction: Young children are at high risk of respiratory infections. The severity of the disease is based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(30 reference statements)
2
2
0
Order By: Relevance
“…On the other hand, the total mean (PRSS) increased on admission day pre and post at 1st, 2nd, 3rd and 4th day among the control group. This result in agreement with Alexandrino et al [13] they found a significant improvement in the total mean PRSS after the management of chest physiotherapy. Generally, our results revealed a positive impact of regular chest percussion for infants suffered from pneumonia which confirmed the correction of the study hypothesis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, the total mean (PRSS) increased on admission day pre and post at 1st, 2nd, 3rd and 4th day among the control group. This result in agreement with Alexandrino et al [13] they found a significant improvement in the total mean PRSS after the management of chest physiotherapy. Generally, our results revealed a positive impact of regular chest percussion for infants suffered from pneumonia which confirmed the correction of the study hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…At 3rd and 4th day post the intervention the highest percent of infants in the intervention group had mild respiratory condition compared to the control group. The results of the current study goes in line with Alexandrino et al [13] found that the highest percent of children presented a moderate respiratory impairment of the respiratory health condition mainly due to the presence of rhinorrhea and secretions. Other study conducted by Nayani et al [24] stated that regarding Clinical Respiratory scores (CRS), about one third of children had mild respiratory condition, more than half in moderate and nine percent in sever category.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PRSS obtained excellent values of content validity (Cronbach's˛= 0.80) and test-retest reliability (ICC 2.1 = 0.91). 13 For nasal auscultation it was used a Littmann 3200 Electronic Stethoscope (3M Health Care ® , USA). Nasal auscultation sounds were collected within a 5 cm distance between the nose and the stethoscope diaphragm in an upright position in relation to the nostrils.…”
Section: Instrumentsmentioning
confidence: 99%